2002
DOI: 10.1090/s0002-9947-02-03013-1
|View full text |Cite
|
Sign up to set email alerts
|

Derivations and invariant forms of Jordan and alternative tori

Abstract: Abstract. Jordan and alternative tori are the coordinate algebras of extended affine Lie algebras of types A 1 and A 2 . In this paper we show that the derivation algebra of a Jordan torus is a semidirect product of the ideal of inner derivations and the subalgebra of central derivations. In the course of proving this result, we investigate derivations of the more general class of division graded Jordan and alternative algebras. We also describe invariant forms of these algebras.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Lie tori with this root-grading type are classified in [BGK,BGKN,Yo1]. It follows from this classification together with [NY,4.9] that L ≃ sl l (Q) for Q a quantum torus in n variables and structure matrix q = (q ij ) an n × n quantum matrix with at least one q ij not a root of unity (3.7).…”
Section: An Interlaced Extension and Letmentioning
confidence: 99%
“…Lie tori with this root-grading type are classified in [BGK,BGKN,Yo1]. It follows from this classification together with [NY,4.9] that L ≃ sl l (Q) for Q a quantum torus in n variables and structure matrix q = (q ij ) an n × n quantum matrix with at least one q ij not a root of unity (3.7).…”
Section: An Interlaced Extension and Letmentioning
confidence: 99%
“…Lie tori with this root-grading type are classified in [BGK,BGKN,Yo1]. It follows from this classification together with [NY,4.9] that L ≃ sl l (k q ) for k q a quantum torus in n variables and q = (q ij ) an n × n quantum matrix with at least one q ij not a root of unity. Ne1,8]) that D induces the Λ-grading of L in the sense that…”
Section: Review: Lie Tori and Ealasmentioning
confidence: 99%
“…For the next lemma we recall that a subset S ⊂ Λ is called a pointed reflection subspace if 0 ∈ S and 2S − S ⊂ S, see for example [NY,2.1], where it is also shown that any pointed reflection subspace is a union of cosets modulo 2Z[S], including the trivial coset 2Z[S]. Here Z[S] denotes the Z-span of S. In particular, a pointed reflection subspace is in general not a subgroup.…”
Section: (Xmentioning
confidence: 99%
“…If A = Z(A) ⊕ [A, A], e.g. if A is a torus ([NY, Prop. 3.3]), then sp 2 (A, π) is centreless and hence is (isomorphic to) the TKK-algebra of the Jordan algebra J = H 2 (A, π) and the Jordan (J, J).Example 7.11.…”
mentioning
confidence: 99%